INCIDENCE OF ACUTE RESPIRATORY DISTRESS SYNDROME IN INTENSIVE CARE UNIT IN THE THREE-MONTH PERIOD: A RETROSPECTIVE STUDY (Fiep Bulletin - online, 2012)
Objetives: To identify the occurrence of acute respiratory distress syndrome (ARDS) in the intensive care unit (ICU). Methods: A retrospective study was performed based on control of respiratory physiotherapy service in the ICU of the University Hospital of the West of Paraná (HUOP). The study period was from March to May 2009. The data collected were: sex, age, cause of admission, duration of mechanical ventilation, type of ARDS (pulmonary or extrapulmonary), the oxygenation index (PaO2/FiO2), the static compliance (CEST), the plateau pressure (Pplat), the response to recruitment maneuver (RM), the prone position, and ultimately, the fate of patients. RESULTS: Of 59 patients admitted in the period, 11 patients had ALI and 20 ARDS. The ICU mortality rate in this period was 38%, and among patients who had ARDS, this rate rose to 70%. The mean (± standard deviation) of PaO2/FiO2 in patients with ARDS was 129.7 (± 39.3). The extrapulmonary ARDS was found in 70% of cases. Conclusion: The incidence of ALI and ARDS in this period was 18.6 and 33.8%, respectively. The main risk factors were sepsis and pneumonia. The mortality rate in patients with ARDS was high.
Keywords: respiration; artificial; respiratory insufficiency; intensive care unit